The Sedimentology and Petrography of the Whirlpool Sandstone (Lower Silurian) in Outcrop and Subsurface in Southern Ontario and Upper New York State - Rutka, Margaret A. (My University, 1986)
The Whirlpool Sandstone (Lower Llandovery) is a thin, sheet-like sandstone, less than 9 m thick, forming the base of the Medina Group in Southern Ontario and western New York. Two very distinct units, a lower and an upper, are recognized in the Whirlpool. The lower unit lacks body and trace fossils, marine microfossils, and wave-formed structures, and is interpreted as being terrestrial in origin. The facies and facies associations, erosional facies relationships, consistent northwest paleocurrents, and lack of lateral and vertical accretion deposits all support a braided fluvial interpretation. Three facies associations, each characterized by different amounts of the trough and ripple cross-laminated and horizontal-laminated facies, are present and are indicative of downstream changes in the river's fluvial style, from a moderately braided river with relatively deep channels in the southeast to a more highly braided river with very shallow channels, in the northwest. Erosional facies relationships and abundant mud intraclasts in the Whirlpool suggest that the river experienced frequent stage fluctuations. The upper unit consists predominantly of interbedded sandstone and shale and bioturbated sandstone, and contains fossils, trace fossils (Skolithos and Cruziana ichnofacies), wave-formed structures and shallow water indicators. The upper Whirlpool formed in a storm-influenced, low-energy nearshore zone of a shallow, low-gradient epeiric sea, where 'normal' wave energy was dissipated some distance from the shoreline. Northwest- to southeast-striking symmetrical ripples indicate that the transgression probably came from the southwest.
The Whirlpool is a moderately spherical, rounded, well-sorted subarkose. No compositional differences exist between the upper and lower Whirlpool. The porosity is secondary, comprises less than 3% of the rock, and shows no regional or vertical trends. Regionally, the Whirlpool's grain size shows an overall fining to the northwest. Vertically, the Whirlpool shows an overall fining upward trend with smaller fining-upward cycles (stacked channelfills) superimposed on this trend. The sandstone's mineralogical and textural maturity suggests a second cycle or multicycle origin. The Oswego Sandstone may be the Whirlpool's source.
A model of lithospheric flexure is used to explain various aspects of the Whirlpool's deposition. Deposition of the fluvial Whirlpool occurred on the northwest side of a northwest-migrating peripheral bulge which formed in response to overthrust loading in the southeast. Complex lithospheric interactions of the Michigan and Appalachian Basins and loading in the south caused the depositional plain to be tilted to the southwest, initiating the transgression over the lower Whirlpool. The presence of a deeper-water facies (Cabot Head Shale) overlying the Whirlpool in the south than in the northwest (Manitoulin Dolomite) suggests that the transgression may have come from the south-southeast, as well.
Title: The Sedimentology and Petrography of the Whirlpool Sandstone (Lower Silurian) in Outcrop and Subsurface in Southern Ontario and Upper New York State, Author: Margaret A. Rutka, Location: Thode